2021
DOI: 10.1002/ajoc.202100413
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dysoxylactam A Using Iterative Homologation of Boronic Esters

Abstract: Dysoxylactam A is a 17‐membered macrocyclic lipid which has been found to dramatically reverse multidrug resistance in cancer cells. Three previous syntheses have been reported in 15–17 steps. Using iterative lithiation‐borylation reactions as the key C−C bond forming and stereocontrolling steps, we now describe an 11‐step synthesis of dysoxylactam A. The complete sequence only required a total of five chromatographic purifications and used minimal protecting groups making it both rapid and efficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…: [ 14 ] –14.1 ( c 0.5, CHCl 3 ); Aggarwal et al . : [ 15 ] –8.0 (c 1.0, CHCl 3 ). 1 H NMR (500 MHz, Chloroform‐ d ) δ : 6.04 (d, J = 8.7 Hz, 1H), 4.81 (d, J = 9.2 Hz, 1H), 4.66 (dt, J = 8.8, 2.9 Hz, 1H), 3.27 (t, J = 7.4 Hz, 1H), 2.40—2.32 (m, 1H), 2.23—2.15 (m, 2H), 1.87 (d, J = 9.8 Hz, 1H), 1.83—1.75 (m, 1H), 1.71 (q, J = 7.0 Hz, 1H), 1.54—1.38 (m, 8H), 1.37—1.06 (m, 9H), 0.98 (dd, J = 6.9, 2.1 Hz, 3H), 0.94—0.84 (m, 15H).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…: [ 14 ] –14.1 ( c 0.5, CHCl 3 ); Aggarwal et al . : [ 15 ] –8.0 (c 1.0, CHCl 3 ). 1 H NMR (500 MHz, Chloroform‐ d ) δ : 6.04 (d, J = 8.7 Hz, 1H), 4.81 (d, J = 9.2 Hz, 1H), 4.66 (dt, J = 8.8, 2.9 Hz, 1H), 3.27 (t, J = 7.4 Hz, 1H), 2.40—2.32 (m, 1H), 2.23—2.15 (m, 2H), 1.87 (d, J = 9.8 Hz, 1H), 1.83—1.75 (m, 1H), 1.71 (q, J = 7.0 Hz, 1H), 1.54—1.38 (m, 8H), 1.37—1.06 (m, 9H), 0.98 (dd, J = 6.9, 2.1 Hz, 3H), 0.94—0.84 (m, 15H).…”
Section: Methodsmentioning
confidence: 99%
“…[ 14 ] Quite recently, Aggarwal and coworkers completed the fourth total synthesis of 1 in 11 steps with about 4.9% overall yield by using iterative lithiation‐borylation reactions as the key C—C bond‐forming and stereo controlling steps. [ 15 ] These synthetic efforts demonstrated that the construction of the…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Ozonolysis with spontaneous lactonisation, followed by oxidation (70% over 2 steps) then afforded (+)-invictolide (49, 16% overall, 8 steps longest linear sequence). The strategy was applied to the total synthesis of serricornin (55) (Fig. 5b).…”
Section: Figure 4 Homologation Of Boronic Esters Using Primary Alkyl ...mentioning
confidence: 99%
“…Recently, organoboron compounds have shown great promise in the automated synthesis of small molecules with high complexity. Some of the remarkable pioneering contributions from the Suginome, Aggarwal, Burke, Crudden, and Tsuchimoto groups have led to the practical application of iterative coupling in the total synthesis of complex natural products and pharmaceuticals. Suginome and other groups ,, demonstrated the iterative coupling capabilities of -Bdan (dan: 1,8-diaminonaphthalene) building blocks employing the Suzuki-Miyaura Coupling (SMC) reaction.…”
mentioning
confidence: 99%
“…Suginome and other groups ,, demonstrated the iterative coupling capabilities of -Bdan (dan: 1,8-diaminonaphthalene) building blocks employing the Suzuki-Miyaura Coupling (SMC) reaction. Burke and co-workers pioneered the automated synthesis of several natural products using -B­(MIDA) ester (MIDA: N -methyliminodiacetic acid) building blocks under SMC conditions. The Aggarwal group developed a unique transition metal-free iterative coupling strategy using the lithiation-borylation sequence in a stereocontrolled manner. …”
mentioning
confidence: 99%